2012
DOI: 10.1002/chem.201202369
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Impact of Atomic Ratio, Charge and Lewis Basicity on Structure Selection and Stability: The Zintl Anion [(La@In2Bi11)(μBi)2(La@In2Bi11)]6−

Abstract: Ternary intermetalloid cluster: the first intermetalloid M/13/15 Zintl anion [(La@In(2)Bi(11))(μ-Bi)(2)(La@In(2)Bi(11))](6-) was obtained upon reaction of [InBi(3)](2-) with [La(C(5)Me(4)H)(3)] in ethane-1,2-diamine. DFT calculations served to analyze and explain the Lewis acid/base interaction upon assignment of formal charges as "Bi(+) ←In(2-) ", which discriminates the anion from an isoelectronic La/Sn/Bi analogue that does not require bridging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 66 publications
0
36
0
7
Order By: Relevance
“… Selected examples of ternary intermetalloid cluster anions. From left: top row: [Zn@Zn 5 Sn 3 Bi 3 @Bi 5 ] 4− ,5a [Eu@Sn 6 Bi 8 ] 4− ,4a [Pd 3 @Sn 8 Bi 6 ] 4− ;5d bottom row: [Pd@Pd 2 Pb 10 Bi 6 ] 4− ,5e [(La@In 2 Bi 11 )(μ‐Bi) 2 (La@In 2 Bi 11 )] 6− 8…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Selected examples of ternary intermetalloid cluster anions. From left: top row: [Zn@Zn 5 Sn 3 Bi 3 @Bi 5 ] 4− ,5a [Eu@Sn 6 Bi 8 ] 4− ,4a [Pd 3 @Sn 8 Bi 6 ] 4− ;5d bottom row: [Pd@Pd 2 Pb 10 Bi 6 ] 4− ,5e [(La@In 2 Bi 11 )(μ‐Bi) 2 (La@In 2 Bi 11 )] 6− 8…”
Section: Methodsmentioning
confidence: 99%
“…However, involving triel atoms (Tr) instead of tetrel atoms, with a formal 2− instead of formal 1− charge per atom, lead to the formation of a “dimeric” anion [(La@In 2 Bi 11 )(μ‐Bi) 2 (La@In 2 Bi 11 )] 6− (Figure 1). 8 Comprehensive quantum chemical investigations demonstrated that this reaction was driven by the necessity to reduce the large charge‐overload at the Lewis basic “In 2− ” sites by Lewis acid–base interactions of the type In 2− →μ‐Bi + ←In 2− .…”
Section: Methodsmentioning
confidence: 99%
“…Other than the E 14 /E 15 Zintl anions, E 13 /E 15 clusters of rare earth cations have also been widely reported, featuring unprecedent structural motifs. For instance, Dehnen and co‐workers reported in 2012 the isolation of an unusual Zintl cluster, [(La@In 2 Bi 11 ) 2 (μ‐Bi 2 )] 6– (Figure A) from the reaction of (C 5 Me 4 H) 3 La and [InBi 3 ] 2– in toluene. X‐ray crystallographic study on the resulted compound revealed the existence of a polyhedral structure consisting of two main‐group‐metal cages: two μ‐Bi bridges were found between the two 13‐vertex In 2 Bi 11 cages encapsulating lanthanum cations (Figure A).…”
Section: Molecular Polybismuthides Of the Rare Earth Elementsmentioning
confidence: 99%
“…Tatsächlich bildet sich auch nur der “[La@In2Bi11]4−”‐Käfig. Aufgrund der wesentlich höheren Basizität des formal vorliegenden In2− verbrückt er aber über zwei Bi‐Atome (formal Bi+) und es bildet sich das Clusteranion {[La@In2Bi11](µ‐Bi)2[La@In2Bi11]}6− (Abbildung 11) 23…”
Section: Multinäre Metallideunclassified